Colonoscopy later than 270 days in a fecal immunochemical test-based population screening program is associated with higher prevalence of colorectal cancer - Zorzi, Manuel; Hassan, Cesare; Capodaglio, Giulia; Baracco, Maddalena; Antonelli, Giulio; Bovo, Emanuela; Rugge, Massimo (Endoscopy, 2020)
Background Colorectal cancer (CRC) screening programs based on fecal immunochemical testing (FIT) generate substantial pressure on colonoscopy capacity in Europe. Thus, a relevant proportion of FIT-positive patients undergo colonoscopy after the recommended 30-day interval, which may be associated with an excess CRC risk.Methods In a cohort of 50–69-year-old patients undergoing biennial rounds of FIT (OC-Hemodia latex agglutination test; cutoff 20 µg hemoglobin/g feces) between 2004 and 2017, we assessed the outcome at colonoscopy (low/high risk adenoma/CRC/advanced stage CRC) among FIT-positive patients, according to different time intervals. The association of each outcome with waiting time, and demographic and clinical factors, was analyzed through multivariable analysis.Results 123 138/154 213 FIT-positive patients (79.8 %) underwent post-FIT colonoscopy. Time to colonoscopy was ≤ 30 days, 31–180 days, and ≥ 181 days in 50 406 (40.9 %), 71 724 (58.3 %), and 1008 (0.8 %) patients, respectively. At colonoscopy, CRC, high risk adenoma, and low risk adenoma were diagnosed in 4813 (3.9 %), 30 500 (24.8 %), and 22 986 (18.7 %) patients, respectively. An increased CRC prevalence at colonoscopy was observed for a time to colonoscopy of ≥ 270 days (odds ratio [OR] 1.75, 95 % confidence interval [CI] 1.15–2.67), whereas it was stable for waiting times of < 180 days. The proportion of advanced CRC also increased after 270 days (OR 2.79, 95 %CI 1.03–7.57). No increase for low or high risk adenomas according to time to colonoscopy was observed.Conclusion In a European FIT-based screening program, post-FIT colonoscopy after 9 months was associated with an increased risk of CRC and CRC progression.